Attentional focus instruction on the hands during bimanual coordination in children with probable developmental coordination disorder - Ferraciola-Gama, Marcela (2023)
Directing attention to one aspect of the bimanual coordination task improves performance. Few studies investigated the effect of attention on the coordination patterns of children with Developmental Coordination Disorder (DCD). Aims: To investigate the effect of attentional focus instructions on the hand on stabilizing bimanual coordination in children with probable DCD. Method: Twenty-eight 9-10 years old children participated in two groups matched by age and gender, based on the results of the Movement Assessment Battery for Children: probable DCD (pDCD) [n=14] and typically developing (TD). Children couple the horizontal movements of the hands in an in-phase coordination pattern, with the attentional focus instruction on the preferred hand, non-preferred hand, and free. Variability of the coupling between the hands and motor control variables were used to assess stability and control strategies adopted by children. Results: Both groups showed more variability concerning in-phase patterns when the attentional focus instruction was on the preferred hand than in other conditions. pDCD showed more variability than TD when the attentional focus instruction was on the non-preferred hand. pDCD performed faster, shorter movements and with more pressure than TD. Conclusion: Attentional focus affected the bimanual coordination patterns of groups, but children with pDCD use different control strategies than TD children. Practical applications: Attentional focus instruction strategies for performing motor tasks, especially tasks that are unfavorable to children with DCD, could help during the motor intervention of this population.